Analisis Tingkat Kreativitas Wirausaha Mahasiswa Melalui Program Komunitas Entrepreneur - Esy Nur Aisyah (Fakultas Ekonomi, UIN Maliki Malang, 2021)
This research is motivated by the Entrepreneur Community Program's existence as support for entrepreneurship courses in the Islamic Banking Department, Faculty of Economics, UIN Maulana Malik Ibrahim Malang to produce graduates who have high selling value, entrepreneurship, and creativity to be able to compete. The learning approach in the program is Project-Based Learning. This study aimed to analyze the level of student creativity before and after participating in the Entrepreneur Community Program. The number of participants was 75 students from the concentration of entrepreneurs in the observation year. Data analysis used nonparametric statistics with Paired-Samples T-Test in testing the creativity of the respondent level before and after treatment and assessing the creativity level of students based on the results of the creativity score generated from the total score filled by respondents divided by the total maximum score of each statement and outlined in the form proportion. The breakthrough research results showed that there were differences in the level of students before and after treatment. The treatment here means that students take part in the entrepreneurial community program with Project-Based Learning. They increased student creativity from 70% to 83%. The level of student creativity before treatment was in the medium category. Moreover, after getting the treatment is in the high category. Thus, project-based learning through the Entrepreneur Community Program in Islamic Banking Department, Faculty of Economics can increase student entrepreneurial creativity.